2019
DOI: 10.1093/ofid/ofz216
|View full text |Cite
|
Sign up to set email alerts
|

No Clinical Benefit to Treating Male Urinary Tract Infection Longer Than Seven Days: An Outpatient Database Study

Abstract: Background The optimal approach for treating outpatient male urinary tract infections (UTIs) is unclear. We studied the current management of male UTI in private outpatient clinics, and we evaluated antibiotic choice, treatment duration, and the outcome of recurrence of UTI. Methods Visits for all male patients 18 years of age and older during 2011–2015 with International Classification of Diseases, Ninth Revision, Clinical M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…As more studies are suggesting shorter optimal antibiotic treatment duration [14,15], our data also suggest no obvious benefit of treatment for more than 7 days. While treatment duration of 7 days or less was associated with higher crude OR for antibiotic switch compared to 8-14 days, the adjusted OR was lower.…”
Section: Treatment Duration and Antibiotic Typementioning
confidence: 51%
See 1 more Smart Citation
“…As more studies are suggesting shorter optimal antibiotic treatment duration [14,15], our data also suggest no obvious benefit of treatment for more than 7 days. While treatment duration of 7 days or less was associated with higher crude OR for antibiotic switch compared to 8-14 days, the adjusted OR was lower.…”
Section: Treatment Duration and Antibiotic Typementioning
confidence: 51%
“…However, there are ongoing discussions regarding the safety and efficacy of treating acute cystitis in male patients as uncomplicated UTIs [13]. Some newer studies suggest that men with acute cystitis do not need treatment for more than 5-7 days [14][15][16], and others argue that nitrofurantoin or pivmecillinam are appropriate as empirical treatment options [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Late-preterm infants who received longer courses of antibiotics had more prolonged alterations in their gut microbiota compared with those who received a shorter duration [26]. There is increasing evidence that a shorter duration of antibiotics of less than 8 days for commonly encountered infections, such as skin and soft tissue infection [27] and male urinary tract infections [28], are not associated with increased treatment failures. Antibiotic stewardship principles of making an accurate diagnosis of infection, appropriate antibiotics, and a shorter duration of antibiotic treatment or prophylaxis, would reduce unnecessary antibiotic exposure to the gut microbiota without compromising patient outcomes [29].…”
Section: Narrowing Antibiotic Spectra and Limiting Duration Of Usementioning
confidence: 99%
“…Antimicrobial Stewardship Broad-spectrum antibiotics can cause significant alteration to the gut microbiota diversity, in particular those with anti-anaerobic activity [8,11] Alterations to the gut microbiota by antibiotics take months to years to restore [24,25] Shorter duration of antibiotic is equally effective than prolonged use and can reduce alterations to the gut microbiota [26][27][28] Oral antibiotics and intravenously administered antibiotics that undergo enterohepatic re-circulation and excretion into bile have a greater impact on the gut microbiota compared to intravenous antibiotics alone [30][31][32][33] Infection Prevention and Control…”
Section: Domain Key Concepts Key Referencesmentioning
confidence: 99%
“…Observational and interventional studies guiding antibiotic stewardship efforts for urinary tract infections (UTIs) are frequently based on information extracted from electronic health records (EHRs) [ 1 , 2 , 3 , 4 ]. Chart review has been shown to be a valid and reliable method for the identification of patients with UTIs.…”
Section: Introductionmentioning
confidence: 99%